ESTÉTICA MUSICAL EMANCIPATÓRIA: A EXPERIÊNCIA DO CHORO EM SÃO PAULO - GARFUNKEL , TEO CARLOS (2016)
This study highlights the potential of non-formal Education as a resource to complement formal Education and an emancipation catalyst when the matter is identity building (individual or collective). Our approach includes theoretical premises from Philosophy, Sociology, Anthropology and Pedagogy and refers to two main authors: Josef Pieper and Theodor Adorno. With a wide epistemological proposal, this study focuses on Choro, urban genre of Brazilian popular instrumental music, and its influence on the cultural formation of a family of Japanese immigrants in São Paulo. It also discusses the concept of Tradition in dialogue with Education and Art, investigating Brazilian culture and its strategies for resistance and emancipation. By putting these elements together, we intend to reinforce the importance of artistic practices in the formation process not only for its relevance in the political sphere, but as a vehicle capable of transcending cultural horizons and everyday’s materialistic pettiness.